A mechanism underlying position-specific regulation of alternative splicing. Issue 21 (9th October 2017) - Hamid, Fursham M.; Makeyev, Eugene V.
Abstract: Many RNA-binding proteins including a master regulator of splicing in developing brain and muscle, polypyrimidine tract-binding protein 1 (PTBP1), can either activate or repress alternative exons depending on the pre-mRNA recruitment position. When bound upstream or within regulated exons PTBP1 tends to promote their skipping, whereas binding to downstream sites often stimulates inclusion. How this switch is orchestrated at the molecular level is poorly understood. Using bioinformatics and biochemical approaches we show that interaction of PTBP1 with downstream intronic sequences can activate natural cassette exons by promoting productive docking of the spliceosomal U1 snRNP to a suboptimal 5′ splice site. Strikingly, introducing upstream PTBP1 sites to this circuitry leads to a potent splicing repression accompanied by the assembly of an exonic ribonucleoprotein complex with a tightly bound U1 but not U2 snRNP. Our data suggest a molecular mechanism underlying the transition between a better-known repressive function of PTBP1 and its role as a bona fide splicing activator. More generally, we argue that the functional outcome of individual RNA contacts made by an RNA-binding protein is subject to extensive context-specific modulation.